Positive Thoughts Positive Action - Arnold Fox (Jaico Publishing House, 2008)
Positive Thoughts Positive Action by Drs. Arnold and Barry Fox can stand alone or be read as the sequel to their co-authored book The Miracle of Positive Thinking. Both books focus on living a positive lifestyle by using action oriented strategies that assist a person in seeing the abundant side of life. Critics insist that these ideas do not work, but the Fox family is proof that what you focus on you become. After you read the heartfelt stories that fill the book, you can decide whether or not this is how you want to live your life.